Bilingual Instruction in Teaching English in Indonesian EFL Classroom - milkayantitudang; Muhammad Basri; Amirullah Abduh (Program Studi Magister Pendidikan Bahasa Inggris, Fakultas Bahasa dan Sastra- Universitas Negeri Makassar., 2024)
The objectives of this research were to find out the teacher’s perceptions of bilingual instruction, the implementation of bilingual instruction, and the impact of bilingual language instruction on students’ English achievement. This research used a qualitative design. The subjects were two teachers at SMA Zion Makassar who participated in this research. This research used an observation checklist, an interview guide, and documentation to collect the data. The results indicated that teachers had a positive perception of bilingual instruction, categorizing it as highly perceived. The teachers executed bilingual instruction effectively. Bilingual instruction had a positive impact on students' English performance and increased their motivation. Thus, the implementation of bilingual instruction has a positive impact and can be an alternative medium for teaching English to EFL students. Keywords: Bilingual instruction, Implementation, Students’ achievement